THE LIBERATION THEOLOGY OF ASGHAR ALI ENGINEER AND ITS RELEVANCE TO ISLAMIC EDUCATION OBJECTIVES - Misbachol Munir; Nida’ul Munafiah (Sunan Kalijaga International Journal on Islamic Educational Research, 2018)
Abstract: Islamic education has a "prophetic” mission as an agent of liberation. The liberation paradigm can be realized with praxis, namely between reflection and action, theory and practice, and faith and charity. Therefore, Islamic education must be able to bear human freedom and social spirit and be able to face challenges amid global life. Asghar Ali Engineer is a progressive Muslim from India trying to understand Islam through liberation theology. The relevance of the theology of the liberation of Asghar Ali Engineer with the aim of Islamic education, with the following formulations: first, education must be able to humanize humans (humanism). Second, Education must be able to liberate people (Liberation), Education at least able to free humanity from three things. Third, education that makes humans capable of realizing Rahmatan Lil Alamin Islam means that education must be able to restore separate human personality in the bondage of materialism dogma that denies human values ​​and is able to restore humanity to its glorious degree, namely through the approach to God Almighty One.